2012
DOI: 10.1097/qmh.0b013e3182417fc4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Real-Time Satisfaction Surveys Through Automated Analysis of Patients' Unstructured Comments and Sentiments

Abstract: possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 11 publications
1
62
0
1
Order By: Relevance
“…This appears to support the argument made by GPs in a previous study [47] as well as physician representatives [68,69] that the majority of Web-based patient feedback is extreme negative opinion. This is usually counteracted in the literature with the statement that studies (including [7,10,20,23,30,35,48,59,70-72]) in and out of the United Kingdom have found that the majority of feedback left on physician review websites is positive [73]. The findings from this study appear to contradict that and further suggest that regardless of whether patient feedback is given on a website or not, patients are much more likely to leave feedback when they have experienced an extreme negative experience.…”
Section: Discussionmentioning
confidence: 99%
“…This appears to support the argument made by GPs in a previous study [47] as well as physician representatives [68,69] that the majority of Web-based patient feedback is extreme negative opinion. This is usually counteracted in the literature with the statement that studies (including [7,10,20,23,30,35,48,59,70-72]) in and out of the United Kingdom have found that the majority of feedback left on physician review websites is positive [73]. The findings from this study appear to contradict that and further suggest that regardless of whether patient feedback is given on a website or not, patients are much more likely to leave feedback when they have experienced an extreme negative experience.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found significant associations between ratings left on websites and clinical outcomes, with better rated hospitals having lower mortality and healthcare associated infection rates 14 15. Early research has demonstrated that sentiment analysis of content in patients’ comments about their care on the internet is feasible 16 17. Sentiment analysis involves taking unstructured, often free-text information, and using software to judge whether the information is broadly positive or negative.…”
Section: Social Media Healthcare Quality and Learning From Other Indmentioning
confidence: 99%
“…Sentiment analysis involves taking unstructured, often free-text information, and using software to judge whether the information is broadly positive or negative. Alemi and colleagues have called for real time patient satisfaction surveys using these analyses 16. Cambria and others believe that individual experiences could be ‘crowd validated’ by aggregating various sources of unstructured information from patients online 18…”
Section: Social Media Healthcare Quality and Learning From Other Indmentioning
confidence: 99%
“…However, processing of text evaluation information is still considered as an accessorial state during the evaluation procedure, and its role has not yet been identified. Substantial research has been carried out regarding the text information problem, which mainly falls in the categories of text clustering (Bouguila, 2011;He, 2011), text mining (Aggarwal, 2012), integration of text information (Henning, 2009;Yin, 2008), text reasoning (Alemi, 2012;Neveol, 2011), recommending systems on the basis of text (Li, 2011), analyzing technique of text abstract (Hien, 2011), and so on. From an analysis of the existing literature, we can conclude that, on one hand, there is ample research on formatted text information in the decision-making process, and that this kind of information can be regarded as a classical form of multi-criterion decision making.…”
Section: Introductionmentioning
confidence: 99%